ÇANAKKALE CEPHESİ'NDE 5.ORDUNUN İAŞESİ - CELOĞLU, YAVUZ SELİM (Fırat Üniveristesi, 2013)
Osmanlı İmparatorluğu?nun I. Dünya Harbinde başarı sağladığı yegane cephe Çanakkale Cephesi?dir. Türk ordusunun kazandığı bu zaferde muharip ordunun kahramanlığı kadar lojistik faaliyetlerin başarılı şekilde yürütülmesinin önemi büyüktür. Zira lojistik destek, tarihin her devirlerinde muharip orduların savaşı devam ettirmesinde adeta can damarı hüviyetindedir. Savaş alanlarındaki lojistik desteğinin yeterliliği stratejiye ve taktiğe ziyadesiyle etki etmekte ve amaca ulaşmanın ancak harekatla lojistik faaliyetlerin birlikte planlanması ve eksikliklerin önceden belirlenip gerekli tedbirlerin alınmasıyla mümkündür.Bu çalışmada, Çanakkale Cephesindeki 5. Ordunun iaşe ve ikmal faaliyetleri ana hatlarıyla arşiv belgeleri ışığında incelenmiş, bu faaliyetlerin mezkûr cephenin kazanılmasındaki yeri ve önemi üzerine odaklanılmıştır. Anahtar Kelimeler: Çanakkale Cephesi, 5. Ordu, Lojistik faaliyetler, İaşe ve İkmal

During World War the First, the only front that The Ottoman Empire was successful was the Gallipoli front. In this victory won by the Turkish army, the successful execution of logistics activities is as of great importance as military heroism. Inasmuch as, for combatant armies to continue the battle, the logistic support is almost like lifeblood in the history of each phase of periods. The adequacy of logistical support in war areas largely influence the strategy and tactics and achieving the goal is only possible when the planning of logistics activities and the acquisition of shortcomings are taken into account together with taking necessary measures.In this study, front, the food and supply activities of 5th Army in Canakkale Front were examined in the light of the archival documents with an outline; and, the importance of these activities on the victory of the front aforementioned was focused on. Key Words: Dardanalle Front, 5th Army, Logistics activities, Food and Supply
Feeding of the 5th army in the battle of Gallipoli
Keywords: Türk İnkılap Tarihi; Tarih